T cell-independent eradication of experimental glioma by intravenous TLR7/8-agonist-loaded nanoparticles - Verena Turco; Kira Pfleiderer; Jessica Hunger; Natalie K. Horvat; Kianush Karimian-Jazi; Katharina Schregel; Manuel Fischer; Gianluca Brugnara; Kristine Jähne; Volker Sturm; Yannik Streibel; Duy Nguyen; et al. (Nature Communications, 2023)
Glioblastoma is a highly aggressive, and also the most common, brain tumour type in adults. Here, the authors generate a nanoparticle encapsulating the TLR7/8 agonist, R848, which induces tumour regression in mice by reprogramming myeloid cells independently of T and NK cells.